POST-DIVORCE PATERNAL CUSTODIAL RIGHTS OF UNDERAGE CHILDREN: LEGAL ANTHROPOLOGY REVIEW - Atik Triratnawati (Fakultas Hukum Universitas Gadjah Mada, 2016)
AbstractThis papers discusses the trend of custodial rights of underage children that fall to the fathers after divorce. The Legal Anthropology Study is conducted by interviewing 15 (ffteen) divorced couples wherein custody fell to the fathers. The tendency of granting custody to the fathers is motivated by several factors from the wives: affairs, ill temperaments, neglectful of children, animosity with the inlaws, and the desire to divorce quickly without the burden to care for children. Fathers accept the responsibility as the caregiver of children to show his economic capability; to easily oversee the development of children; to facilitate their daughters when they require custodians for their marriage as well as to provide affections. In caring for children, fathers are assisted by relatives.Intisari Tulisan ini membahas tren hak asuh anak di bawah umur pasca perceraian jatuh di tangan bapak. Studi Antropologi Hukum dilakukan dengan mewawancara 15 pasangan cerai dengan hak pengasuhan jatuh ke tangan bapak. Kecenderungan pengasuhan anak ke tangan bapak dilatarbelakangi faktor istri: selingkuh, tabiat buruk, penelantaran anak, bermusuhan pada mertua perempuan, ingin cepat bercerai tanpa beban mengasuh anak. Bapak menerima tanggung jawab sebagai pengasuh anak karena ingin menunjukkan bahwa ia mampu secara ekonomi; agar mudah mengawasi tumbuh kembang anak; memudahkan saat anak perempuannya nanti membutuhkan dirinya sebagai wali nikah serta ingin mencurahkan kasih sayang. Bapak mengasuh anak dengan bantuan kerabatnya.